Line Flux Characterization of Galaxies in the Green Valley (2025)
In this work, we use spectroscopic and photometric data from the Sloan Digital Sky Survey to study the spectrophotometric properties of galaxies in the nearby universe. We introduce a new quantity, we call it the “Spectral Line Ratio Space” created by the ratio of flux of spectral lines in galaxies, both absorption and emission, aiming to identify features of galaxies in the color magnitude diagram. This quantity identifies in a unique form, a galaxy as a vector defined by the ratio of their spectral lines, by combining all possible ratios between emission line fluxes and absorption indices, and all galaxies span a full space defined by this N-dimensional vector (being N the number of spectral lines used), thus defining two separate parameter spaces. For emission tracers, a clear decrease in [OIII] 5007 is observed in blue, star-forming galaxies, stabilizing at lower values in intermediate and red colors. However, a subset of red galaxies exhibits enhanced emission due to active galactic nuclei (AGN). Combined ratios such as ([OII] + [OII])/[OIII] 5007 and ([SII] + [SII])/[OIII] 5007 differentiate two clusters within the red sequence: passive red galaxies and AGN-hosting galaxies with enhanced [OIII] 5007 emission. In this context, we introduce a “robust” criterion to identify objects classified as AGN using spectral line features. Using this criterion, a group of non-AGN-classified galaxies displays AGN behavior along the emission tracers and is an interesting target for future studies. For absorption tracers, Hδ and the Mg1 index emerge as key indicators, revealing two regions of enhanced absorption activity directly associated with AGN hosts. We perform a cluster analysis in the n-dimensional space defined by the ratio of spectral lines. This analysis confirms the expected bimodality in the CMD, emphasizing a difference between emission and absorption-line spaces. In the blue-sequence of the color distribution 62% of the galaxies identified through absorption ratios coincide with the emission-based clustering, while an 85.2% agreement is found in the red sequence. A population of transition galaxies emerges from the mixed clustering results in the blue sequences, suggesting an evolutionary link between the blue and red sequences, and allowing to identify galaxies in the Green Valley not only by their colors, but through their clustering and Hβ (emission)/D4000 <100 spectral line ratio values.